BURNOUT DAN PENTINGNYA MANAJEMEN BEBAN KERJA - Edy Purwo Saputro; Fereshti Nurdiana (Benefit: Jurnal Manajemen dan Bisnis, 2005)
Globalization that requires efficiency and productivity in all aspects results variousconsequences, including demand to finish any work in a very limited time. It emerges several effects,whether individually or in teamwork. If this condition is not managed properly, it may turn upwork stress. Of course, it can be fatal and therefore, proper management of working load is neededto minimize that condition.